2020
DOI: 10.1016/j.aninu.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of Bacillus subtilis PB6 improves sow reproductive performance and reduces piglet birth intervals

Abstract: We investigated the effects of dietary supplementation with Bacillus subtilis PB6 ( B. subtilis PB6) during late gestation and lactation on sow reproductive performance, antioxidant indices, and gut microbiota. A total of 32 healthy Landrace × Yorkshire sows on d 90 of gestation were randomly assigned to 2 groups, with 16 replicates per group, receiving basal diet (CON) or the basal diet + 0.2% B. subtilis PB6, containing 4.0 × 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 67 publications
(73 reference statements)
9
55
0
1
Order By: Relevance
“…The increased relative abundance of Firmicutes is beneficial to intestinal health, as it contains a large number of SCFA-producing bacteria, such as butyrate-producer Eubacterium rectale and Eubacterium Hallii , which help to maintain intestinal health [ 30 ]. Actinobacteria is reported to be part of the symbiosis intestinal microbiota, but a high proportion of Actinobacteria is associated with intestinal inflammatory diseases and colon cancer [ 31 ]. Therefore, our results suggested that GOS could increase the relative abundance of Firmicutes and decrease the relative abundance of Actinobacteria in the colonic mucosa of LPS-challenged piglets.…”
Section: Discussionmentioning
confidence: 99%
“…The increased relative abundance of Firmicutes is beneficial to intestinal health, as it contains a large number of SCFA-producing bacteria, such as butyrate-producer Eubacterium rectale and Eubacterium Hallii , which help to maintain intestinal health [ 30 ]. Actinobacteria is reported to be part of the symbiosis intestinal microbiota, but a high proportion of Actinobacteria is associated with intestinal inflammatory diseases and colon cancer [ 31 ]. Therefore, our results suggested that GOS could increase the relative abundance of Firmicutes and decrease the relative abundance of Actinobacteria in the colonic mucosa of LPS-challenged piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Increased relative abundance of Firmicutes is bene cial to intestinal health, as it contains a large number of SCFAproducing bacteria, such as butyrate-producer Eubacterium rectale and Eubacterium Hallii, which help to maintain intestinal health 21 . Actinobacteria is reported to be part of the symbiosis intestinal microbiota, but a high proportion of Actinobacteria is associated with intestinal in ammatory diseases and colon cancer 22 . Therefore, our results suggested that GOS could increased the relative abundance of Firmicutes and decreased the relative abundance of Actinobacteria in the colonic mucosa of LPSchallenged piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Existem diversos tipos de microrganismos utilizados como probióticos, com destaque são os dos gêneros Lactobacillus, Bifidobacterium, Enterococcus, Bacillus e leveduras (Zhang et al, 2020). Existem peculiaridades dos microrganismos para que esses possam vir a ser utilizados como probióticos, são: fazer parte da flora já existente no hospedeiro, ter alta capacidade de sobrevivência e colonização, ter boa capacidade de ligação ao epitélio intestinal, sobreviver à ação de enzimas digestivas do hospedeiro, não ser tóxicos ou patogênicos, ser cultivável em escala industrial, ser comerciável e estimular a capacidade imune do hospedeiro (Souza et al, 2020).…”
Section: Influência Dos Aditivos Na Saúde Intestinal Dos Suínosunclassified